Entre lembrar e conhecer: um estudo de Teeteto - Almeida, Vitor Rodrigues de (2022)
The discussion in the Theaetetus is about the nature of knowledge, and although the dialogue does not deal directly with the nature of memory, this problem is present throughout the discussion. So, it seems that there is an important relationship between knowledge and memory in this dialogue. The question that we will address in this dissertation is how this relationship occurs and what it consists of. To answer these questions, we will present the discussion brought up in the dialogue in which Socrates helps the young Theaetetus to give light to his own ideas about knowledge. The first idea is that knowledge is perception, the second idea is that knowledge is true judgment, and the third idea is that knowledge is true judgment plus reason (logos). All ideas are examined and refuted throughout the dialogue, which ends up inconclusive. This presentation will follow the interpretations of authors such as Cornford (1935), Burnyeat (1990), and Sedley (2002), in view of the meaning that knowing has in the dialogue. From there we will go on to some considerations about the possible skepticism of Socrates, mainly pointed out by Annas (1992), which serves as motivation for a re-reading of the Theaetetus which emphasizes the meaning that remembering has in the dialogue. In this way, we hope to show that what exists between remembering and knowing is the activity of learning, based on education.